2019
DOI: 10.1016/j.adolescence.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health experiences, knowledge and understanding in low SES female teenagers: A diary approach

Abstract: Introduction: Understanding how teenagers think about sexual health and assessing the ways in which they engage with sexual health information are important issues in the development of appropriate sexual health education programmes. Sexual health education programs in the UK are inconsistent and is not possible to assume that teenagers' information needs are being met by such programs. Teenagers often feel uncomfortable discussing sexual health making it difficult to assess teenagers' understanding and engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Teenagers have incomplete information about sexual topics, while shame, embarrassment, lack of sufficient self-esteem, and fear of being judged also prevent them from raising sexual questions. Other studies also confirmed these findings (14)(15)(16)(19)(20)(21)28). According to the insufficient knowledge of families, the study results revealed that parents lacking sufficient information about sexual health agree with the results of the study by Simber et al, considering the awareness and need for family sex education (15).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Teenagers have incomplete information about sexual topics, while shame, embarrassment, lack of sufficient self-esteem, and fear of being judged also prevent them from raising sexual questions. Other studies also confirmed these findings (14)(15)(16)(19)(20)(21)28). According to the insufficient knowledge of families, the study results revealed that parents lacking sufficient information about sexual health agree with the results of the study by Simber et al, considering the awareness and need for family sex education (15).…”
Section: Discussionsupporting
confidence: 53%
“…Some studies have focused on sexual health education barriers and facilitators among Iranian teenage boys (13,14), assessment of sexual education needs (15,16), barriers to health education in schools (17), and the girls' challenges in seeking information and the fertility health (18,19). Some global studies have also been performed about sexual health information-seeking obstacles and challenges on the internet (20,21), information sources (22), sexual health information-seeking results (3), and technology usage (23,24).…”
Section: Introductionmentioning
confidence: 99%